PERBEDAAN KUALITAS TANAMAN MINT (Mentha spicata L) HIDROPONIK DAN KONVENSIONAL BERDASARKAN MORFOLOGI TANAMAN, PROFIL KROMATOGRAM, DAN KADAR MINYAK ATSIRI - Pratiwi, Pramita Yuli; Mardiyaningsih, Ana; Widarti, Emi (Jurnal Riset Kefarmasian Indonesia, 2019)
Mint is one of the essential oil-producing plants. Essential oils of Mentha spicata L or spearmint are widely used as raw materials in the food, beverage and pharmaceutical preparations industries. The main components of spearmint are karvon, limonen, cineol, dihydrocarvol, myrcene, and 0.5% menthol. The components contained in spearmint have properties as herbal remedies. Plant cultivation greatly determined the results of standardized drug ingredients. Cultivation with the right planting system can affect the quality of simplicia. This research were a descriptive study to differentiate the quality of plants. This study aimed to determine differences in plant morphology, chromatogram profile and levels of spearmint essential oil between hydroponic and conventional planting systems. Observation of plant morphology includes the size, color of the stem and leaves. Essential oil content is calculated from refined oil by steam and water distillation method. Spearmint oil was analyzed on thin layer chromatography methode using the silica gel F254 as a stationary phase and hexane-ethyl acetate (8: 2) as a mobile phase, with spot visualization under UV254 and anisaldehyde-H2SO4 . The results showed that the morphology of Mentha spicata L with hydrophonic planting systems had a bigger size in stem and leaves, but the leaves had more bright green than a conventional plant. The chromatogram profile did not show differences in the number of spots and Rf. Mentha spicata L with conventional planting systems had a sharper intensity of color on one of the volatile oil spot, and suggested due to menthol. The levels volatile oil of Mentha spicata L hydroponic and conventional were determined as 0.0326% and 0.0323% . The Independent T-test analysis showed that there were not a significant differences.